Observation on changes of trace elements and amino acids in serum of patients with hepatocellular carcinoma - LUO Xi, JIANG Yongmei, MA Di, LU Qiuya, GU Xiaohan (Waike lilun yu shijian)
Objective To explore the changes in trace elements and amino acid profiles in serum of patients with hepatocellular carcinoma(HCC) providing a reference for clinical diagnosis and treatment.Methods A total of 104 patients with HCC who underwent surgical treatment in the Department of Hepatobiliary Surgery of our hospital from January 2024 to April 2024 were selected as the study group, and 139 patients with benign biliary diseases during the same period were selected as the control group. Atomic absorption spectrometry was used to detect the levels of six trace elements (copper, zinc, calcium, magnesium, iron, and lead) in the serum of both groups, and liquid chromatography-tandem mass spectrometry was used to measure the concentrations of 21 amino acids.Results Compared with the control group, the serum copper level in the HCC group was significantly increased (P<0.05), while the levels of zinc and iron were significantly decreased (P<0.05). Amino acid profile analysis revealed that, compared with the control group, the concentrations of tyrosine, methionine, and phenylalanine in the HCC group were increased (P<0.05), while the concentrations of valine, leucine, isoleucine, glutamine, and arginine were decreased (P<0.05). Further analysis of the correlation between trace elements and amino acids with statistical differences between the groups showed that copper was negatively correlated with valine and leucine (P<0.05), while zinc and iron were positively correlated with valine, leucine, and isoleucine (P<0.01).Conclusions Imbalances in trace elements and amino acid metabolism changes are common in patients with HCC, and there may be an intrinsic connection between the two.